Rekonstruksi Hukum Kewarisan Beda Agama Ditinjau dari Al-UshÅ«l Al-Khamsah - Tohari, Chamim (IAIN Samarinda, 2017)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Islamic Inheritance Law is believed to be a law containing rules that are in line with public interest. Hence, only few Moslem scholars (ulamaâ€™) have conducted ijtihad on the topic in order to reform its rules and bring them pursuant to contemporary situation. Consequently, when there is a gap between the ideal of Islamic inheritance law (i.e. maslaha) and its application in the Islamic society, a rational ruling over the problem of inheritance division faced by Moslems becomes unavailable. Given this, it is necessary to re-interprete the textual sources of Islamic Inheritance Law, in order to come up new rules pursuant to the objective of syariâ€™ah. One of the pressing problems need to be resolved is about the status of Muslim heirs whose inherits from their non-Moslem family. This article thus discusses two main issues: first, what the opinions of Moslems scholars are about a Moslem who inherits from his/her non-Moslem family; and second, which opinion is the most relevant to the al-uá¹£hÅ«l al-khamsah. This article is doctrinal legal research which employs comparative and deductive analysis. It reveals that: (1) the Moslem scholars are devided into two groups of thought, the first group forbid a Moslem to inherit from his/her non-Moslem family, and the second group allow it; (2) the most relevant opinion to the objective of syari`ah is the second opinion. This is so because the admissibility of a Moslem to inherit from his/her non-Moslem fulfils the criteria of public interest of essential and complimentary level.Â Keywords: Islamic Inheritance law, interfaith inheritance law, istiá¹£lÄhi, al-uá¹£Å«l al-khamsah.Â Â